Analisis Literatur Tentang Prinsip Bernoulli Dalam Desain Aliran Fluida - Harefa, Daman; Giawa, Andel (CV. SINAR HOWUHOWU, 2025)
The design of Bernoulli's law experiment tool was designed for finding out the relationship between the pressure and the speed of the fluid’s flow according Bernoulli's law statements and know the standard deviation of Bernoulli's law tool. This tool was designed based on the basic and principle of ideal fluid flowing through a pipe from the fisrt bottle into the second bottle which hung on a statif modification. Design of this tool were simple so it was easy to do experiment. The experiment results were do twice where the first experiment applied on the condition both of firs bottleand second bottle was same in height and for the second experiment the first bottle and the second bottle was different in height. The first experiment showed the water would stop for flowing when the high of water in the first bottle and second bottle were the same unless for the second experiment the water was stops flowing when the difference height of water in the bottle as same as the difference between the first bottle’s height with the second bottle’s height. The result of experiment proved the tool that has designed showed the level of error for the first experiment was 6.97% with the average speed of the fluid’s flow (43 ± 2) 10-3 cm3/s and the error level for second experiment was 9.99% with the average speed of the fluid’s flow (43 ± 3) 10-3 cm3/s.